THE CORRELATION OF CHOLESTROL, LDL, AND HDL SERUM LEVEL WITH THE FORMATION OF GALLSTONE - Arlan, Alsen; Singh, Sarup; Manawan, Efman EU; Komar, M. Hafidh; Febriansyah, Bobby (International Journal of Psychosocial Rehabilitation, 2020)
Background: Gallstones disease is one of the major problems which occurrence is commonly related to gender, age, diet and obesity. However, the prevalence varies between population where 10-15% cases were reported in the Europe but only 3-5% in African and Asian population which might lead to the assumption that distinctive causal factors affecting different populations. Thus, this research will study the risk factors of gallstone formation primarily focusing on small population in Palembang, Indonesia.Objective: This study aims to evaluate the prevalence and possible risk factors for gallstone disease by focusing on influence of the level of cholesterol, high density lipid (HDL) and low-density lipid (LDL).Method: This case control study was performed on 32 patients with cholecystitis receiving treatment at Dr. Mohammad Hoesin General Hospital from October to December 2019 and the data was compared with the same number of samples in control group to assess any significant association.Result: The data from patients in the case group which have the confirmed cases of cholecystitis recorded a high level of cholesterol and LDL level. However, low HDL level was recorded in the case group as compared to the control group. The level of cholesterol, high LDL and low HDL level is a significant risk factor for the formation of gallbladder stone and cholecystitis.Conclusion: High cholesterol and LDL level can be an indicator for the formation of gallbladder stone which can also lead to the inflammation known as cholecystitis. HDL on the other hand has a protecting factor which the level its inversely associated with cholecystitis formation.